Experimental and computational study of flapping wing aerodynamics at low reynolds number - Chai, Vincent Wee Sern (2013)
Recent rapid developments in micro-sized Unmanned Aerial Vehicles (UAVs) and Underwater Vehicles (UWVs) have attracted renewed research interest in flapping wings aerodynamics. Due to the limitation of the size of these vehicles, complex motions employed by the birds and fishes have to be simplified as additional actuators are needed to perform the complex motions which will significantly increase the size of these vehicles. In addition, the study of flapping wings aerodynamic is challenging as the parameters involved that affecting the performance is huge. Therefore, this thesis investigates the feasibility of flapping wings with simplified kinematic motions as the propulsion system for the micro UAV or UWV and obtains the optimizing parameters for improving the flapping wings aerodynamics performance through experimental and numerical simulation approaches. A simple analytical model for predicting the lift with moderate accuracy is also developed. In conclusion, with comprehensive works conducted, a better understanding of the physics behind the flapping wings aerodynamics allows the translation of knowledge and creates great impact to the development of flapping wings micro UAV and UWV.